Nonlinear TE-polarized surface polaritons supported by graphene - Bludov, Yuliy V. (2014)
We analyze the propagation of electromagnetic waves along the surface of a nonlinear dielectric medium covered by a graphene layer. We reveal that this system can support and stabilize nonlinear transverse electric (TE) plasmon polaritons. We demonstrate that these nonlinear TE modes have a subwavelength localization in the direction perpendicular to the surface, with the intensity much higher than that of an incident wave which excites the polariton.